The development of the high ability child psychological perspectives on giftedness - Miller, Erin M.; Matthews, Michael S. 1968-.; Dixson, Dante D. 1989-. (Oxon, OX Routledge, 2022)
"This valuable text will help readers to understand the physical, social and cognitive development of high ability children. Written by experts in the fields of education and psychology, each chapter applies core principles of psychology to the development of gifted and talented children. Through the content, readers will be shown how these children are like all children as well as the ways in which their development is unique. Covering the psychology of learning and learners, personality differences, language and physical development, problem solving and motivation of high ability children, this book provides readers with a strong foundation for supporting and developing advanced learners. The text also includes Field Notes and Eye for Diversity sections to enable readers to put into practice, and recognize, important issues being discussed. Throughout, the editors blend discussions of research with practical advice for individuals charged with nurturing children with advanced cognitive potential. It is an essential read for students, counsellors, administrators, therapists and parents seeking to support high ability children and their needs"--Provided by publisher.
Includes bibliographical references and index
Keywords: Gifted children -- Education; Child psychology; Educational psychology